Investigating the effects of low input drying procedures on maize (Zea mays L.), cowpea (Vigna unguiculata L.) and bambara groundnut (Vigna subterranea (L.) Verdc.) seed quality in benin - Dako Enoch, A.=700 1 Ehsan, D.M.; Sognon, V.; Florent, E.
(En, Fr, Es)
ilus., 24 ref.
Keywords: SECADO; SEMILLAS; ZEA MAYS; VIGNA UNGUICULATA; VIGNA SUBTERRANEA; CALIDAD; CONTENIDO DE HUMEDAD; ITALIA